Experimental Study of Photovoltaic System Conversion into Thermal Energy Using 50 Wp Solar Module - Nadjib, Muhammad; Wahyudi, Wahyudi; Thoharudin, Thoharudin (Universitas Muhammadiyah Yogyakarta, 2025)
The battery is the most vital component in a photovoltaic system. Under high solar irradiation, the battery may experience overcharging, primarily if the voltage limiter in the battery charge controller is not functioning correctly. To prevent excessive voltage buildup, the electrical energy is redirected for use in a water heating system. This study aims to experimentally examine the conversion of electrical energy from solar modules into thermal energy for heating water. The experiment was conducted outdoors using a photovoltaic setup comprising a 50 Wp solar module, a 10 A battery charge controller, and a 70 Ah battery. The water heating system includes a 25-liter water tank, a DC pump, an electric heater, a flowmeter, and piping components. Data were collected on solar module current and voltage, solar irradiation, and water temperature. The analysis shows that electrical power, thermal energy, and water temperature increase with higher solar irradiation. Throughout the experiment, the battery remained protected from overcharging. This energy conversion system successfully produced hot water at a maximum temperature of 37.68°C under an average solar irradiation of 586.31 W/m².